Sistema eleitoral proporcional : uma proposta técnico-politica para o Brasil - Dantas, Sivanildo de Araújo (2006)
The present work aims to analyze the several proportional electoral systems from the contemporaries democracies in order to, in the end, purpose a system that better fits to the constitutional Brazilian order. In this direction, we pursued to indicate the main virtues and imperfections in proportional electoral systems in use in more than two hundred countries, especially relating to the positive and negative effects that these systems inject in the party systems, in the governability and in the representativity. In order to collect elements, and also before getting to the work s main point, other issues were approached, even in a shortened way. Nevertheless, in a position taking, we conclude the work opting for a proportional electoral system that potencializes the constitutional principles of representativity and governability as well as prints a party system strong and strict, once these are the depositaries of a democracy compromised with the Brazilian society